Effect of tobacco in human oral leukoplakia: a cytomorphometric analysis - Patel, Uday; Shah, Rina; Patel, Alpesh; Shah, Shreyas; Patel, Dhruva; Patel, Anil (Medicine and Pharmacy Reports, 2020)
Objectives. Tobacco use is one of the most critical risk factors for different oral diseases. The aim of this study is to demonstrate the effect of tobacco on oral mucosa by cytomorphometric analysis of cells with the help of exfoliative cytology and to find out the improvement in diagnostic sensitivity of exfoliative cytology in the detection of dysplastic changes and early oral malignancy. Methods. The nuclear area (NA) and cytoplasmic area (CA) of cells were measured within cytological smear obtained from leukoplakia lesions of buccal mucosa of 90 tobacco users, 30 smokers (TS), 30 chewers (TC) and 30 with combined habit of smoking and chewing (TSC)] and from normal buccal mucosa of 30 non users (NU) of tobacco. Each habit group consisted of 30 tobacco users with oral leukoplakia lesion with mild epithelial dysplasia only. The 30 non-users of tobacco served as controls. The mean values of the CA and NA were obtained for each case, and the nuclear/cytoplasmic area (NA/CA) ratio was calculated. Results. The results showed a statistically significant increase (P<0.001) in mean NA and a statistically significant decrease (P<0.001) in mean CA values of tobacco users with leukoplakia as compared to non-users, hence NA/CA ratio value was significantly higher in tobacco users with the lesion. Conclusion. The changes in cellular morphology caused by tobacco use can be visualized by use of exfoliative cytology with the help of cytomorphometric analysis. The evaluation of parameters (NA, CA and NA/CA ratio) may increase the sensitivity of exfoliative cytology for the early diagnosis of oral premalignant and malignant lesions.